Evaluating a collaborative smoking cessation intervention in primary care (ENTER): study protocol for a cluster-randomized controlled trial - Härter, Martin (Trials, 2015)
BACKGROUND: Tobacco consumption is a preventable risk factor for chronic disease and complicates the treatment of medical conditions. Therefore, the German health insurance company AOK NORDWEST has developed a collaborative smoking cessation intervention for individuals with cardiovascular disease, chronic obstructive pulmonary disease and heavy smokers, with the aim of reducing tobacco consumption. The objective of the study ENTER is to evaluate the effectiveness of the collaborative smoking cessation intervention and determine its cost-effectiveness. METHODS/DESIGN: This study is a cluster-randomized controlled trial conducted with 40 medical practices that are being selected from different geographic regions in Germany. Participating medical practices will be randomly allocated to either the intervention or control group. Within the medical practices, a total of 800 patients will be recruited for participation in the study and blinded to group assignment. Patients are included in the study if they are 18 years or older, insured by AOK, heavy smokers (smoke at least 20 cigarettes per day) and/or suffer from chronic obstructive pulmonary disease or cardiovascular disease. Exclusion criteria are patients who are nonsmokers, who have cognitive impairments or who are illiterate. Physicians from medical practices in the intervention group will motivate patients to participate in a smoking cessation program offered by the health insurance, refer them to the program and ask about their program participation. Physicians from medical practices in the control group will provide usual care. Data collection will take place on the date of study inclusion and after 6 and 12 months. The primary outcome is the amount of cigarettes consumed during the past 30 days, 12 months after the initial medical consultation. Secondary outcomes are abstinence from smoking, health-related quality of life and respiratory complaints. Moreover, a process evaluation and health economic analysis will be performed. DISCUSSION: The results of this study will help to determine whether the collaborative smoking cessation intervention is an effective and feasible way to promote smoking cessation in the primary care setting and provide evidence regarding its cost-effectiveness. TRIAL REGISTRATION: German Clinical Trials Register DRKS00006079. Registered 4 June 2014.